Dilute initial dentofacial abscess of buccal space: a technical note - Berardi, Rogerio Henrique; Ogoshi, José Lineu Pereira; Horikawa, Fernando Kendi; Yokoyama, Plinio Jun Iti; Snidei, Iron Ricardo Machado; Shinohara, Elio Hitoshi (ARCHIVES OF HEALTH INVESTIGATION, 2021)
The treatment of the dentofacial abscess was always surgical because the evacuation of the purulent collection and removal of the cause are mandatory. Large abscesses, especially those that reach the submandibular space, require laboratory and imaging exams, but small abscesses restricted to the buccal space can be successfully treated by diluting the purulent collection with saline solution using needle and syringe.